THE HISTORY OF ROBERT GROSSETESTE'S TRANSLATIONS WITHIN THE CONTEXT OF ARISTOTELES LATINUS. - Devriese, Lisa (Revista Española de Filosofía Medieval, 2023)
Among his many accomplishments, Grosseteste is known for translating Greek philosophical, theological, and glossarial treatises into Latin, making them available for Latin readers. Three of these translations are nowadays studied for the Aristoteles Latinus project, which aims at making critical editions of all Greek-Latin medieval translations of Aristotle's oeuvre. The goal of this contribution is to give an overview of the history of Robert Grosseteste's translations of Aristotelian texts within the context of Aristoteles Latinus. The first part is devoted to previous research on these translations and to a status quaestionis of current scholarship. The second part turns its focus to Grosseteste's characteristic translation method. It offers new insights into the usual translation of certain smaller Greek words (such as particles and conjunctions) into Latin by Grosseteste, and what can set this translator apart from other medieval translators.